2023
DOI: 10.5826/dpc.1301a67
|View full text |Cite
|
Sign up to set email alerts
|

International Dermoscopy Society (IDS) criteria for skin tumors: validation for skin of color through a Delphi expert consensus by the “Imaging in Skin of Color” IDS Task Force

Abstract: Introduction: A structured set of eight basic dermoscopic parameters (lines, clods, dots, circles, pseudopods, structureless, else, and vessels) including a total of 77 variables with corresponding descriptive and metaphoric vocabulary has been released for evaluation of skin tumors by the International Dermoscopy Society (IDS). Objectives: To validate the aforementioned criteria for the use in darker phototypes (phototypes IV-VI) via an expert consensus. Methods: The two-round “Delphi method” was adopted, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Various nationwide surveys and pan-continental studies from other continents reported dermoscopy use ranging from 56.9 % to 98% [ 5 , 9 11 , 23 26 , 28 31 ]. Despite widespread awareness of its dermatological utility, dermoscopy use was predictably lower (50%) than in Western societies This observation aligns with the evolving role of dermoscopy in diagnosing skin conditions in individuals with darker skin phototypes, a population largely represented in Africa [ 21 , 22 , 32 , 33 ]. Historically, dermoscopy had been used exclusively for distinguishing neoplastic lesions from pigmented and non-pigmented benign lesions in lighter skin phototypes [ 34 ].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Various nationwide surveys and pan-continental studies from other continents reported dermoscopy use ranging from 56.9 % to 98% [ 5 , 9 11 , 23 26 , 28 31 ]. Despite widespread awareness of its dermatological utility, dermoscopy use was predictably lower (50%) than in Western societies This observation aligns with the evolving role of dermoscopy in diagnosing skin conditions in individuals with darker skin phototypes, a population largely represented in Africa [ 21 , 22 , 32 , 33 ]. Historically, dermoscopy had been used exclusively for distinguishing neoplastic lesions from pigmented and non-pigmented benign lesions in lighter skin phototypes [ 34 ].…”
Section: Discussionmentioning
confidence: 69%
“…There are however relatively few studies on dermoscopic features of skin lesions in the darker skin phenotypes [ 15 , 16 , 20 ]. Until recently, there has not been standardized terminologies for the dermoscopy of skin lesions in skin of color [ 21 , 22 ]. However, in order to demonstrate the diagnostic utility of dermoscopy and formulate useful diagnostic criteria in darker skin types, many more studies from this population are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, available information for some tumors concerns only some tones of “dark skin” spectrum (especially phototype IV). Nevertheless, the possible correspondence between histopathological changes of cutaneous tumors and dermoscopic findings even in skin of color makes oncological dermoscopy a potential useful aid in dark phototypes too [ 8 ]. Future comprehensive studies using a homogeneous/standardized approach will help in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Dermatoscopy is a precious tool for dermatologists, enabling an assessment of skin lesions based on patterns, structures, signs and colors and significantly facilitating the clinicaldiagnosis. In SoC, different color backgrounds and patterns typical of darker phototypes maybe alter the dermoscopic aspect, as compared to white skin [ 4 ]. The combination between ‘skin of colour” and ‘dermatoscopy” Pubmed search results in 680 articles with limited research in the dermatoscopy of skin cancer in SoC patients.…”
Section: Introductionmentioning
confidence: 99%